Effects of a Planned Behavior Program via Smartphone Applications on Asthma Care Behavior and Asthma Symptom Control in School-age Children with Asthma - Karanyapassakul, Nattakan; Nookong, Apawan; Srichantaranit, Arunrat (Nursing Science Journal of Thailand, 2024)
Purpose: To study the effects of a planned behavior program via smartphone applications on asthma care behavior and asthma symptom control in school-age children with asthma. Design: Quasi-experimental research. Methods: The sample included 50 school-aged children from easy asthma clinics at 2 hospitals in Nakhon Pathom province. The participants were assigned into the control group (N = 25) and experimental group (N = 25) matched by age and level of asthma symptom control. In the 8-week program period, the control group received usual care, and the experimental group received a planned behavior program via smartphone applications, which employed Ajzen planned behavior theory. The instruments were asthma symptom control questionnaires and asthma care behavior questionnaires. Data were analyzed by independent t-test and a chi-square test. Main findings: The results revealed that the experimental group had significantly higher scores of asthma care behavior than the control group. (t = 4.46, p < .001), and the experimental group had a significantly higher percentage of children with asthma symptom control levels than those in the control group. ( 2 = 7.22, p < .05). Conclusion and recommendations: It has been shown that a planned behavior program via smartphone applications can improve asthma care behaviors and levels of asthma symptoms control in school-aged children with asthma. Health care personnel should apply the program to promote asthma care behavior and symptom control among school-aged children with asthma.